2020
DOI: 10.33545/pathol.2020.v3.i3c.273
|View full text |Cite
|
Sign up to set email alerts
|

WT1, Bcl-2, Ki-67 and Her2/Neu as diagnostic and prognostic immuno markers in ovarian serous and endometrioid carcinoma

Abstract: Background: Ovarian cancer is the fifth common cause of death due to cancer in women. It constitutes 3% of all cancers in females and 15-20% of genital malignancies. Most of the ovarian cancers are serous type followed by endometrioid type. Sometimes glands of these two carcinomas are indistinguishable histologically. It also becomes difficult to differentiate these two types when they are poorly differentiated. Aims: The aim of this study was to find out differences in immuno-markers expressions between serou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that WT1 can be used as an important marker for the diagnosis and prognosis of ovarian cancer (Basak et al;Taube et al, 2016;Gaaib, 2018;Sallum et al, 2018;Mondal et al, 2021). Our research has identified related genes and signaling pathways in ovarian cancer that are affected by WT1, and identified genes that are associated with WT1 and affect the prognosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have shown that WT1 can be used as an important marker for the diagnosis and prognosis of ovarian cancer (Basak et al;Taube et al, 2016;Gaaib, 2018;Sallum et al, 2018;Mondal et al, 2021). Our research has identified related genes and signaling pathways in ovarian cancer that are affected by WT1, and identified genes that are associated with WT1 and affect the prognosis of ovarian cancer.…”
Section: Discussionmentioning
confidence: 74%